Upper and lower body anaerobic performance of semi-elite Rugby League players - Lovell, D. I.; Mason, D.; Delphinus, E.; McLellan, C. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of this study was to measure the upper and lower body anaerobic performance of semi-elite Rugby League (RL) players. Methods: Twenty-two semi-professional RL players and 24 physically active but untrained men completed two Wingate anaerobic tests (WAnT) on an electronic arm ergometer and a cycle ergometer separated by three days. Percent body fat was used determined from the sum of six skinfolds and upper and lower muscle cross-sectional area (CSA) was calculated from anthropometric data. Results: Upper and lower body absolute peak (P=0.035, P=0.002) and mean (P=0.005, P=0.031) power were higher in the RL group compared to the control group. Upper and lower body relative peak power was higher (P=0.022, P=0.047) in the control group compared to the RL group. Peak and mean power (relative and absolute) were higher (P=0.05) in the lower body compared to the upper body. Peak and mean power relative to upper and lower muscle CSA was higher (P=0.001) in the upper body compared to the lower body for both groups. Conclusion: Semi-elite Rugby League players have well developed absolute anaerobic power, but relative to body weight upper and lower body anaerobic power is not well developed. The upper body is able to generate more power relative to body weight and muscle CSA compared to the lower body during the WAnT. Future studies should examine the upper body anaerobic performance of elite RL players and other sports that have similar upper body demands.